MACHANICAL ANALYSIS AND SIMULATION STUDY ON THE MIDDLE GROOVE CONNECTION SYSTEM OF SCRAPER CONVEYOR - ZHANG DongSheng; YU HaiYang; JIANG JiaNing; LI Yan; SONG ZhenDuo (Jixie qiangdu)
In this paper,the central groove scraper conveyor connecting system as the research object,the mechanics model of middle groove connection system different postures,and were to push the slide and Lycra two kinds of stress conditions in central groove connection system were analyzed. ANSYS software simulation analysis of its static strength and fatigue life,results showed that the central groove connection system weakest place in the passage of the ear and dumbbells fossa,fossa stress concentration dumbbell caused by this result and the actual work damage convex tip matches and proposed to increase the size of the dumbbell nest rounded to reduce stress concentration and reduce stress peaks to resolve this issue. The study was designed scraper conveyor system connecting central groove provides a reference and theoretical basis.